RATIONALLY INJECTIVE MODULES - Abbas, Mehdi Sadiq; Nayef, Mahdi Saleh (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this work we introduce the concept of rationally injective module, which is a proper generalization of (essentially)-injective modules. Several properties and characterizations have been given. In part of this work, we find sufficient conditions for a direct sum of two rationally extending modules to be rationally extending. Finally we generalize some known results.